Kajian Kriminologi Terhadap Kasus Pembunuhan Seorang Bayi Oleh Ibu Kandung - Dian Wulan Ramadhani; Johny Krisnan; Basri Basri; Yulia Kurniaty (Universitas Muhammadiyah Magelang, 2022)
Unwanted pregnancies often end in unlawful acts such as illegal abortions, murder, or the disposal of the baby by the birth mother. Therefore, this study aims to find out